Improvement of Physical and Chemical Soil Quality of Oil Palm Plantation through Integrated Farming System of Cattle and Oil Palm to Achieve Sustainable Agriculture - Romelah, Siti; Niswati, Ainin; Tugiyono, Tugiyono; Dermiyati, Dermiyati (JOURNAL OF TROPICAL SOILS, 2017)
The objectives of the research were to compare the quality of physical and chemical characteristics of the soils in the oil palm plantations applied with integrated farming system of cattle and oil palm plantation (IFSCO) and without IFSCO (non-IFSCO), as well as to evaluate the economic benefits of IFSCO application. The research was conducted in two oil palm plantations, i.e. an oil palm plantation applied with IFSCO (5 ha) and an oil palm plantation without IFSCO application (non-IFSCO) (5 ha), located in the Karya Makmur Village, Penawar Aji Subdistrict, Tulang Bawang District, Lampung, Indonesia, in June until August 2016. The research was conducted using a survey and systematic sampling methods to collect soil samples, and data from 30 farmers who applied IFSCO and other 30 farmers who applied non-IFSCO. The results showed that the application of organic fertilizer in the IFSCO field resulted in higher level of exchangeable-K, -Ca, -Mg, and -Na, cation exchange capacity (CEC), and organic-C content of the soil;and better improvement on the physical soil quality, i.e. bulk density, porosity and soil moisture content; in comparison to that in the field without organic fertilizer application (non-IFSCO field). However, the application of IFSCO did not affect the pH, available-P, base saturation and total-N content of the soil.Â  There was a difference in the texture class of the soils in the IFSCO field and non-IFSCO field.Â  The result of texture analysis showed that the texture of the soil in the IFSCO field is â€œclayâ€, while the texture of the soil in the non-IFSCO field is â€œsandy clay loamâ€.Â  Application of IFSCO can save the fertilizer cost by 66%, the feed cost by 50%, and can increase oil palm production and farmersâ€™ income by about 25%, so it is economically profitable. Thus, IFSCO can improve soil quality and provide economic benefits for the farmers, so the IFSCO obviously supports the implementation of sustainable agriculture.